2016
DOI: 10.1111/apm.12511
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity toward bacterial stimuli in patients with age‐related macular degeneration

Abstract: Although the pathogenesis of age-related macular degeneration (AMD) is unclear, genetic screening has revealed that polymorphisms in the complement system may be associated with AMD development. Production of autoantibodies was also found in AMD patients. In this study, we analyzed the antibody response in AMD patients. We found that purified B cells from AMD patients tended to respond to lower concentrations of bacterial antigen stimulation, and produced higher amounts of antibodies, especially in IgM and IgA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…But there are no significant differences in AMD compared with healthy individuals [134]. A study suggested that B cells from advanced AMD patients secret higher levels of antibodies to fight bacterial antigens, especially including IgM, IgG and IgA, and more sensitive to the more diluted concentration of bacterial antigens [135]. However, the relationship and mechanisms between B lymphocytes and AMD still remain unclear and further investigations are needed.…”
Section: B Lymphocytesmentioning
confidence: 99%
“…But there are no significant differences in AMD compared with healthy individuals [134]. A study suggested that B cells from advanced AMD patients secret higher levels of antibodies to fight bacterial antigens, especially including IgM, IgG and IgA, and more sensitive to the more diluted concentration of bacterial antigens [135]. However, the relationship and mechanisms between B lymphocytes and AMD still remain unclear and further investigations are needed.…”
Section: B Lymphocytesmentioning
confidence: 99%
“…However, studies have shown that the Th1/Th2 ratio is an independent predictor of VEGF plasma levels in diabetic retinopathy [ 363 ]. Other studies suggest that Th17 cell-dependent IL-17 may be associated with the inflammation observed in diabetic retinopathy [ 46 , 48 , 148 ]. IL-17A has been shown to be an important detrimental cytokine in the progression of diabetic retinopathy [ 253 , 254 ].…”
Section: Adaptive Immunity and Diabetic Retinopathymentioning
confidence: 99%
“…It remains in question whether they are a consequence of disease-related damage or a contributory factor for the disease development [ 157 , 158 , 160 ]. In contrast, studies have also shown no difference in the number of circulating B lymphocytes in AMD patients when compared with healthy subjects, which does not rule out B lymphocytes involvement in AMD pathology because antibody production by B lymphocytes could still have a contributory effect [ 46 , 48 ]. Studies have also suggested that autoantibodies could be used as biomarkers for future disease progression and prognostication [ 157 , 158 , 160 , 218 ].…”
Section: Adaptive Immunity and Age-related Macular Degenerationmentioning
confidence: 99%
“…In most cases of geographic atrophy, some degree of increased signal from RPE is observed in FAF imaging in the junctional zone of the atrophic lesion and in adjacent retina without atrophy. 16 Under normal conditions, microglia serves as the resident immune cells in the central nervous system (CNS) and in the retina, protecting the neurons from damage. 5,6 The reason for hyperautofluorescence prior to cell death is unclear, but the increased signal can be explained by changes in RPE cells, such as increased intracellular concentration of lipofuscin, loss of protective melanosomes, RPE dysmorphia resulting in taller cells or RPE migration leading to stacked cells.…”
Section: Introductionmentioning
confidence: 99%
“…14 Furthermore, natural killer cells are demonstrated to promote CNV formation, 15 and B cells from donors with AMD tend to be more sensitive to antigen-stimulation. 16 Under normal conditions, microglia serves as the resident immune cells in the central nervous system (CNS) and in the retina, protecting the neurons from damage. Young microglia have a ramified morphology, and are evenly distributed in the inner layers of the retina.…”
Section: Introductionmentioning
confidence: 99%